Stand out of my sunlight: The mediating role of climate change conspiracy beliefs in the relationship between national collective narcissism and acceptance of climate science. (August 2021) - Bertin, Paul; Nera, Kenzo; Hamer, Katarzyna; Uhl-Haedicke, Isabella; Delouvée, Sylvain
Despite the scientific consensus about the anthropogenic nature of climate change, there are still obstacles hindering society from acknowledging the severity of the situation. Notably, previous research suggests that climate change threats can cause people to display ethnocentric reactions to preserve the ingroup's interests. In this research, we investigate the relation between collective narcissism and attitudes towards climate science. We argue that national collective narcissism is negatively associated with the acceptance of climate science. We further hypothesized that this relation might be mediated by conspiracy beliefs about climate change, because narcissistic identifiers are prone to hold conspiracy beliefs. In a pilot study ( N = 409), we found that national collective narcissism was significantly associated with climate change conspiracy beliefs. In Study 1 ( N = 295), climate change conspiracy beliefs mediated the negative relation between national collective narcissism and acceptance of climate science. In Study 2 ( N = 375), this mediation was replicated when controlling for other forms of climate skepticism. Lastly, general conspiracy mentality did not mediate this relation, which emphasizes the importance of considering the specificity of climate change conspiracy theories (rather than generic propensity to believe in conspiracy theories) in understanding distrust of climate science.